PENGARUH SENAM DYSMINORE TERHADAP PENURUNAN SKALA NYERI PADA MAHASISWI DI KAMPUS STIKES PELITA IBU - Nur Afni; Fajar Kurniawan (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2023)
Special attention should be paid to reproductive health, especially among adolescents, especially women. Dysmenorrhea is pain experienced in adolescence. The causes of dysmenorrhea are levels of the hormone progesterone, prostaglandins, and stress/factors. Exercise for dysmenorrhea can prevent it. Dysmenorrhea gymnastics is a technique that guarantees comfortable and stress-free conditions during dysmenorrhea. The body produces endorphins during exercise. The purpose of this study was to the Effect of Dysminore Gymnastics on Reducing Pain Scale in Female Students at STIKes Pelita Ibu Campus. This study used pre-experimental research methods. Conducted on 161 students with a research period of 3 days and a sampling technique, namely accidental sampling. The results of the analysis using the McNemar Test X2 value calculated 103,221 > 3.841 and p value 0.000 < 0.05, meaning dysminore exercise has an effect on reducing menstrual pain. It was concluded that there was an influence of Dysminore Gymnastics on Decreasing the Pain Scale in Female Students at the STIKes Pelita Ibu Campus. It is recommended the need for increased education for women and especially menstrual pain sufferers where by improving exercise routines both before menstruation and while menstruation is highly recommended as a prevention of menstrual pain which has an impact on limiting activities.